Mathematical concepts exploration of gamelan musical instruments and dance movements in Kuda Lumping Wanareja - Amalia, Rizka Nur; Fatimah, Ai Tusi; Amam, Asep (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
This research explored mathematical concepts of Gamelan musical instruments and dance movements in Kuda Lumping Wanareja. This research used a qualitative approach with an ethnographic design. Located of research at Cihandiwung Lor, Adimulya, Wanareja, Cilacap, Central Java. Data was collected through observation, interviews, and documentation. Data were analyzed through reduction, presentation, and verification of conclusions. The research results showed that Wanareja's Kuda Lumping gamelan musical instruments consisted of kendang, demung, saron, calapita, kenong, bonang, kethuk, drum, gong, and kempul. Based on the shape of gamelan musical instruments, mathematical concepts include numbers, measurement, and geometry. The saron, demung, bonang, and kempul contain the concept of natural numbers, while kempul shows the concept of quantity. The kendang, demung, saron, calapita, kenong, bonang, kethuk, drum, gong, and kempul show the concept of a rectangle, circle, trapezoid, and tube. The layout of gamelan musical instruments (especially bonang) involves a matrix concept. The Kuda Lumping dance consists of ngatur sembah, pecak pedhang, losing to the enemy, fighting against the enemy from the right, fighting against the enemy from the left, ending the battle, mejang beksa, and janturan/mendem. The mathematical concept related to dance movement patterns is geometric transformation (reflection, translation, and rotation). Several dance movements for praying, breaking the sword, losing to the enemy, fighting against the enemy, and ending the battle show reflection and translation. The janturan and mejang beksa dance movements show rotation. Concerning Gamelan musical instruments, there are kethuk and saron which show two-dimensional geometric concepts such as circles and trapezoids. The results of this research are applied as context in mathematical problems.